Making learning meaningful: facilitating interest development and transfer in at-risk college students. Issue 5 (28th May 2017) - Heddy, Benjamin C.; Sinatra, Gale M.; Seli, Helena; Taasoobshirazi, Gita; Mukhopadhyay, Ananya
Abstract: The Teaching for Transformative Experience in Science (TTES) model has shown to be a useful tool to generate learning and engagement in science. We investigated the effectiveness of TTES for facilitating transformative experience (TE), learning, the development of topic interest and transfer of course concepts to other courses employing a quasi-experimental design. Our goal was to determine the effectiveness of TTES compared to an alternative teaching method in a course designed for academically at-risk undergraduate students. Specifically, we explored the impact of TTES for teaching about motivation in a college success course. The results showed that TTES generated TE outside of the biological sciences, increased learning, developed student interest and facilitated self-reported transfer to other courses. The findings have important implications for facilitating learning and motivation in academically at-risk college students, which may subsequently impact college student retention and academic success.